Właściwość sądu w postępowaniu w sprawie o ustalenie czy orzeczenie sądu państwa obcego podlega albo nie podlega uznaniu według Kodeksu postępowania cywilnego - Derdak, Mateusz (PRAWO i WIĘŹ, 2026)
This paper addresses issues concerning court jurisdiction in proceedings to determine whether a foreign judgment is recognised.  The need to discuss this topic stems from the fact that, as regards jurisdiction, the provisions in Title I of Book Three, Part Four of the Code of Civil Procedure, which govern the recognition of judgments of courts of foreign states or decisions of other foreign authorities, are limited to the succinct rule set out in Article 1148^1 § 1 of the Code of Civil Procedure (CCP).  Under that provision, an application for a determination that a judgment of a court of a foreign state is, or is not, subject to recognition is examined by the regional court that would have local jurisdiction to hear the case decided by the foreign court, or in whose circuit the locally competent district court is situated; failing such a basis, jurisdiction lies with the Regional Court in Warsaw. The doubts relate primarily to the method of determining the local jurisdiction of the court in this category of cases, in particular how to interpret the wording used in Article 1148^1 § 1 CCP: „the court locally competent to hear the case decided by the court of a foreign state or in whose circuit the locally competent district court is situated”. Given the topic of the article as framed above, it is also relevant to consider the court’s examination of jurisdiction in proceedings to determine whether a ruling of a foreign judgment is or is not recognised.